Morning light cleanup and recovery operation: simulation studies of possible reactor fuels. [Cosmos 954 orbiting Russian reactor with U-10 wt% Mo fuel] - Landingham, R. L.; Casey, A. W. (Lawrence Livermore Laboratory, 1978)
The nuclear fuel for Cosmos 954, the orbiting Russian reactor that broke up on reentry during January of 1978, has been identified as a U--Mo alloy containing about 10 wt% molybdenum. Identification was based on a combination of simulation studies at LLL, examination of fuel debris at Whiteshell Nuclear Research Establishment (WNRE), Pinawa, Manitoba, and reactor technology knowledge. In the LLL simulation studies, mixtures of uranium, molybdenum, and UO/sub 2/ were heated under conditions that simulated reentry and then examined by scanning electron microscopy, energy dispersive spectrometry, and x-ray diffraction. These studies indicated metallic behavior and suggested a U--Mo alloy. The identification was useful in assisting the Canadians in recovery, cleanup, and health/safety activities associated with the radioactive debris, which was scattered over a wide region of the Great Slave Lake.